Pengaruh Penggunaan Teknologi Dalam Pembelajaran Terhadap Kemampuan Kognitif Anak Usia Dini - Mawarda, Salwa Isya; Fadilah, Syifa Nur; Zahra, Jasmine Amani; F, Fidrayani (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The use of technology in learning has a significant impact on the cognitive development of young children in kindergarten. This research found that the use of technology can improve children's cognitive abilities in various ways, such as increasing the ability to understand abstract symbols, improving the ability to remember, and increasing the ability to express opinions. The use of technology can also help children think logically, quickly and grasp, as well as increase their imagination and idea abilities. Additionally, technology can help children develop important cognitive skills, such as the ability to relate, initiate, and consider events. Thus, the use of technology in learning can be an effective strategy for improving the cognitive abilities of young children in kindergarten.